Pengaruh Latihan Daya Ledak Tungkai Terhadap Lompat Jauh Gaya Jongkok Pada Siswa Kelas XI SMA Negeri 5 Tidore Kepulauan - Isnardi Ismail; La Rusmin Simal (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to determine the effect of limb explosive power on the squat style long jump in class XI students of SMA Negeri 5 Tidore Kepulauan, and how much influence the two variables have on each other. This research was carried out at SMA Negeri 5 Tidore Kepulauan with a sample of 20 students of class XI. The results of the calculation of test data from the two variables of the effect of limb explosive power on the squat style long jump in class XI students of SMA Negeri 5 Tidore Islands can be obtained t count = 7.541 this result is then compared with t table at significance level = 0.05 with dk = n-1 that is equal to 1.729 and at = 0.1 which is equal to 2.539. Thus tcount = 7.541> t table 1.729. Then it was concluded that the hypothesis (H1) was accepted and rejected the hypothesis (H0), which means that the proposed research hypothesis can be accepted, namely that there is an effect of limb explosive power training on the squat-style long jump in class XI students of SMA Negeri 5 Tidore Islands.